2010
DOI: 10.1111/j.1360-0443.2010.02917.x
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on Salmon et al. (2010): The case for safer inhalation facilities—waiting to inhale

Abstract: Commentary on Salmon et al. (2010):The case for safer inhalation facilities-waiting to inhalea dd_2917 684..685 In recent years, a flurry of scholarly reports have demonstrated the effectiveness of supervised injection facilities (SIFs) as a strategy to reduce physical and social harms associated with injection drug use. Empirical data on SIFs lagged well behind their scale-up, but SIFs have now been shown to decrease HIV risk behaviors [1], overdose deaths [2] and public disorder [3], and increase uptake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As DCF services have been implemented (in Europe) or discussed (in the Americas) in several jurisdictions, this is a major gap for evidence-based intervention development and implementation aiming at crack users. Rigorous studies should urgently be implemented to determine whether DCF services could constitute a potentially beneficial intervention for health and other outcomes, yet also for improving crack users' integration with the help system (Fischer et al, 2006;Hedrich et al, 2010;Strathdee & Navarro, 2010 On the treatment side, a substantive body of -fairly welldesigned and controlled -studies suggests that psycho-social (e.g., cognitive-behavioral) treatment interventions can reduce drug use and health risks/harms, as well as improve social indicators for crack-cocaine use, at least to some extent. While studies are commonly limited in regards to treatment retention and a predominant focus on short-term effects, there appears to be a trend for tailored and more intensive interventions to result in superior efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As DCF services have been implemented (in Europe) or discussed (in the Americas) in several jurisdictions, this is a major gap for evidence-based intervention development and implementation aiming at crack users. Rigorous studies should urgently be implemented to determine whether DCF services could constitute a potentially beneficial intervention for health and other outcomes, yet also for improving crack users' integration with the help system (Fischer et al, 2006;Hedrich et al, 2010;Strathdee & Navarro, 2010 On the treatment side, a substantive body of -fairly welldesigned and controlled -studies suggests that psycho-social (e.g., cognitive-behavioral) treatment interventions can reduce drug use and health risks/harms, as well as improve social indicators for crack-cocaine use, at least to some extent. While studies are commonly limited in regards to treatment retention and a predominant focus on short-term effects, there appears to be a trend for tailored and more intensive interventions to result in superior efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A series of Canadian studies -conducted in Vancouver, Toronto and Ottawa -have found that largely majorities (ranging from 28% and 71%) of street-involved crack and other drug inhalers would use DCF services if offered, but did not measure any impacts of such interventions (Bayoumi et al, 2012;Collins et al, 2005;DeBeck et al, 2011;Shannon et al, 2006). Unfortunately, overall no rigorous evaluations on the discernable impacts of DCF programs targeting drug inhalers -including crack users -exist (Hedrich et al, 2010;Strathdee & Navarro, 2010).…”
Section: Material/environmental Interventions: Drug Consumption Facilmentioning
confidence: 98%
See 1 more Smart Citation
“…Collectively, these findings suggest the potential for evidence-based public health interventions to reduce the harms associated with public crack use and rushed public crack use. While the evidence in support of supervised injection facilities is now well-established [ 41 45 ], the implementation of supervised inhalation rooms has been slow to follow suit, despite the overwhelming benefit that such facilities may offer in terms of providing a safe, non-rushed environment; sterile equipment to prevent disease transmission; direct access to health and social services for this hard-to-engage population prone to fatal overdose, infection, and other complex health concerns; immediate support for addiction treatment and counselling; reducing public drug use and related disorder; and affording considerable cost savings for health care systems [ 15 , 46 – 49 ]. Notably, the implementation of supervised inhalation rooms need not be separate from supervised injection facilities; in fact, the delivery of both supervised injection and inhalation (or other non-injection drug use) in a single ‘safe drug use facility’ may be a more feasible and accessible approach for this population.…”
Section: Discussionmentioning
confidence: 99%
“…As such, several jurisdictions have implemented SIFs, and there are currently 92 facilities in 61 cities globally . Nevertheless, SIFs remain highly controversial in many parts of the world .…”
Section: Introductionmentioning
confidence: 99%